2014
DOI: 10.14202/vetworld.2014.38-43
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal acidosis- A case compilation study in SAQ Teaching Veterinary Hospital, Bangladesh

Abstract: Materials and Methods: A total of 609 clinical cases were considered during the study period and the diagnosis of the cases was performed based on detailed history, clinical signs, and clinical examinations including color, odor and consistency of rumen fluid and rumen microflora movements. The confirmations of the cases were done by measuring the pH of the rumen fluid and the blood. Calcium level of blood was measured by biochemical analyzer to determine hypocalcaemia. Results:The overall prevalence of rumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
(3 reference statements)
4
6
0
Order By: Relevance
“…Results showed maximum protein (3.62±0.12) percent in milk of group B and minimum (3.22±0.09%) in the group C. However there was no significant variation in protein (%) between A, B, C, D and E groups. These results are in line with reported findings of [5,13]. Lactose content was found maximum (4.54±0.35%) in group E and minimum (3.94±0.27%) in group B.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Results showed maximum protein (3.62±0.12) percent in milk of group B and minimum (3.22±0.09%) in the group C. However there was no significant variation in protein (%) between A, B, C, D and E groups. These results are in line with reported findings of [5,13]. Lactose content was found maximum (4.54±0.35%) in group E and minimum (3.94±0.27%) in group B.…”
Section: Resultssupporting
confidence: 93%
“…It is shown in the table that the maximum total solids (13.64±0.24%) was observed in the group E and minimum (13.39±0.14%) was recorded in group B. However there was significant variation in total solids (%) among group A, D and E, while non-significant variation between group B and C. [11][12][13][14][15][16][17][18] also reported relevant kinds of findings when studied milk composition in relation with different dietary composition. Senn [12,14,15,17,18] reported finding are also supportive to current study results.…”
Section: Resultsmentioning
confidence: 99%
“…All goats after the treatment with Cassia fistula passed the feces within 3hrs, and started feeding within 12hrs of treatment, pH increased sharply. Goats with lactic acidosis containing ruminal fluid with watery consistency and souring odor, these findings were found to be in close connection with [25]. Further, the blood glucose level was found increased after the ingestion of grains this indicated that the grain feed was converted into highly fermentable action of the rumen microbial flora, these results are similar to [26].…”
Section: Discussionsupporting
confidence: 55%
“…ivestock plays an important role in the national economy of Bangladesh with direct contribution of around 8% to the agricultural GDP and providing 32% of total employment in the economy of Bangladesh (Alam et al, 2014). It is also declared that cattle of Bangladesh are an indivisible and essential part of the agricultural farming and agribusiness (Ahmed et al, 2010).…”
mentioning
confidence: 99%
“…As far known all the study were includes a cross section of animals from the terminal market (Market where the cattle are transported), without considering the initial market (The market from where transportation started) before transportation, hence the changes in biomarkers due to transportation are not clearly identified. Furthermore, most of the previous study in Bangladesh were limited to identification of physical injuries (Alam et al, 2014;Kober et al, 2014) and some were includes some biochemical parameters (Alam et al, 2010b). So it is utmost important to conduct a comprehensive study covering the physical injury and haematological status both before and after transportation of cattle.…”
mentioning
confidence: 99%